Arthropod Distribution in a Tropical Rainforest: Tackling a Four Dimensional Puzzle - Basset, Yves; Cizek, Lukas; Cuénoud, Philippe; Didham, Raphael K; Novotny, Vojtech; Ødegaard, Frode; Roslin, Tomas; Tishechkin, Alexey K; Schmidl, Jürgen; Winchester, Neville N; Roubik, David W; Aberlenc, Henri-Pierre; et al. (PLoS One, 2015)
Quantifying the spatio-temporal distribution of arthropods in tropical rainforests represents a first step towards scrutinizing the global distribution of biodiversity on Earth. To date most studies have focused on narrow taxonomic groups or lack a design that allows partitioning of the components of diversity. Here, we consider an exceptionally large dataset (113,952 individuals representing 5,858 species), obtained from the San Lorenzo forest in Panama, where the phylogenetic breadth of arthropod taxa was surveyed using 14 protocols targeting the soil, litter, understory, lower and upper canopy habitats, replicated across seasons in 2003 and 2004. This dataset is used to explore the relative influence of horizontal, vertical and seasonal drivers of arthropod distribution in this forest. We considered arthropod abundance, observed and estimated species richness, additive decomposition of species richness, multiplicative partitioning of species diversity, variation in species composition, species turnover and guild structure as components of diversity. At the scale of our study (2 km of distance, 40 m in height and 400 days), the effects related to the vertical and seasonal dimensions were most important. Most adult arthropods were collected from the soil/litter or the upper canopy and species richness was highest in the canopy. We compared the distribution of arthropods and trees within our study system. Effects related to the seasonal dimension were stronger for arthropods than for trees. We conclude that: (1) models of beta diversity developed for tropical trees are unlikely to be applicable to tropical arthropods; (2) it is imperative that estimates of global biodiversity derived from mass collecting of arthropods in tropical rainforests embrace the strong vertical and seasonal partitioning observed here; and (3) given the high species turnover observed between seasons, global climate change may have severe consequences for rainforest arthropods.
Keywords: Ecosystem; Tropical Climate; Animal Distribution; Arthropods; členovci; Panama; Animals; tropické klima; Rainforest; biodiverzita; rozšíření zvířat; Phylogeny; zvířata; fylogeneze; deštný prales; ekosystém; Biodiversity